The Impact of Mandated Disclosure on Performance‐Based CEO Compensation* - CRAIGHEAD, JANE A.; MAGNAN, MICHEL L.; THORNE, LINDA (Contemporary Accounting Research, 2004)
Abstract Regulators argue that mandated compensation disclosure improves corporate governance by permitting shareholders to enjoin boards of directors to reward executives in ways that are consistent with shareholder value creation. We posit that mandated compensation disclosure, or the absence thereof, has a greater impact on the CEO compensation practices of widely held firms than of closely held firms. More specifically, we expect that, in the absence of mandated disclosure, CEO compensation is likely to be less performance‐contingent among widely held firms than among closely held firms. Moreover, we also expect that the advent of mandated disclosure leads widely held firms to increase the extent to which CEO compensation is performance‐contingent, much more so than closely held firms would. We use a unique data base resulting from the Ontario Securities Commission amendment of regulation 638 in October 1993. For the first time, this amendment required firms listed on the Toronto Stock Exchange to provide detailed executive compensation data similar to those required by the Securities and Exchange Commission, for the current year as well as retroactively for the previous two years. We find that, in the absence of mandated disclosure, CEO cash compensation in widely held firms is less performance‐contingent than in closely held firms. With the imposition of mandated disclosure, performance‐contingent cash compensation increases more in widely held firms than in closely held firms. Results with respect to stock option grants are mixed, with both closely held and widely held firms reacting to the advent of mandated disclosure.